Multi-branched Cu2O nanowires for photocatalytic degradation of methyl orange. (28th March 2018) - Yu, Chunxin; Shu, Yun; Zhou, Xiaowei; Ren, Yang; Liu, Zhu
Abstract: Multi-branched cuprous oxide nanowires (Cu2 O NWs) were prepared by one-step hydrothermal method of a facile process. The architecture of these Cu2 O NWs was examined by scanning electron microscopy, and the resulting crystal nanowire consists of the trunk growing along [100] plane and the branch growing along [110] plane. Photocatalytic degradation of methyl orange (MO) in the experiment indicates that pure Cu2 O NWs prepared at 150 °C have a higher photocatalytic activity (90% MO were degraded within 20 min without the presence of H2 O2 ) compared with the samples obtained at other temperatures. In the photoelectrochemical test, pure Cu2 O NWs had outstanding photoelectric response, which corresponds to the catalytic performance. The superior photocatalytic performance can be attributed to the absence of grain boundaries between the small branches and the nanowire trunk, which is conducive to the transport of photo-generated carriers, and the reduction of Cu impurities to reduce the number of recombination centers.